2014
DOI: 10.1212/wnl.0000000000001012
|View full text |Cite
|
Sign up to set email alerts
|

Global investigation and meta-analysis of the C9orf72 (G 4 C 2 ) n repeat in Parkinson disease

Abstract: Objectives:The objective of this study is to clarify the role of (G4C2)n expansions in the etiology of Parkinson disease (PD) in the worldwide multicenter Genetic Epidemiology of Parkinson's Disease (GEO-PD) cohort.Methods:C9orf72 (G4C2)n repeats were assessed in a GEO-PD cohort of 7,494 patients diagnosed with PD and 5,886 neurologically healthy control individuals ascertained in Europe, Asia, North America, and Australia.Results:A pathogenic (G4C2)n>60 expansion was detected in only 4 patients with PD (4/7,2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
41
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 31 publications
7
41
0
1
Order By: Relevance
“…The cohort size suggested an association for the 10-unit repeat and for pooled alleles of ≥17 repeats in increasing PD risk, but this did not reach significance after correction for multiple testing. 38 In nine atypical parkinsonian disease studies, including pathologically confirmed multiple system atrophy (MSA) 21 39 and diffuse Lewy body dementia (DLB) 40 41 cases, pathogenic expansions were rare, and repeat range of non-expansion alleles were similar to that of controls. 14 17 21 30 33 39 42 Two pathologically diagnosed DLB samples carried 32 repeats and one with 33 repeats, although no details were provided regarding presence or absence of TDP43 pathology in these patients.…”
Section: Original Articlementioning
confidence: 99%
“…The cohort size suggested an association for the 10-unit repeat and for pooled alleles of ≥17 repeats in increasing PD risk, but this did not reach significance after correction for multiple testing. 38 In nine atypical parkinsonian disease studies, including pathologically confirmed multiple system atrophy (MSA) 21 39 and diffuse Lewy body dementia (DLB) 40 41 cases, pathogenic expansions were rare, and repeat range of non-expansion alleles were similar to that of controls. 14 17 21 30 33 39 42 Two pathologically diagnosed DLB samples carried 32 repeats and one with 33 repeats, although no details were provided regarding presence or absence of TDP43 pathology in these patients.…”
Section: Original Articlementioning
confidence: 99%
“…Although several studies have investigated the presence of large C9ORF72 repeat expansions in Parkinson disease (PD) or atypical parkinsonisms, its pathogenic role in these disease is not clear [12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Almost all of the C9ORF72 expansion carriers presented with gait difficulties. Recently, it has been suggested that the full or intermediate (20–30 repeats) C9ORF72 expansion could be associated with Parkinson’s disease [14], but the results were not replicated in an autopsy-confirmed study setting or meta-analysis of published research [12, 15]. However, a connection between atypical Parkinsonian disorders that potentially cause problems with gait (progressive supranuclear palsy, multiple system atrophy and cortico-basal degeneration) and intermediate number of repeats has been found in many papers [16-20].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of bvFTD was based on the Rascovsky et al [6] criteria. Patients who simultaneously presented with at least one of the three core symptoms associated with iNPH, together with enlarged ventricles disproportionate to the size of the sulci of the cerebral convexities (Evan’s index > 0.30) [12] based on CT or MRI scans, were referred to a neurosurgeon. Subsequently, a 24-h intraventricular pressure (IVP) monitoring, spinal tap, or lumbar infusion test was performed by a neurosurgeon.…”
Section: Methodsmentioning
confidence: 99%